Characterizing Student-Driven Research Investigations Contributed to the GLOBE Program Citizen Science Initiative in a Formal Education Context - Ann Martin; Katherine Miller-Bains; Julie Malmberg; Lin Chambers; Kevin Czajkowski (Citizen Science: Theory and Practice, 2022)
The Global Learning and Observations to Benefit the Environment (GLOBE) Program offers citizen science opportunities to participants of all ages, with a focus on youth in formal classroom contexts. This study uses student investigation research reports and posters submitted to the 2018 International Virtual Science Symposium (IVSS) and Student Research Symposium (SRS) as testbeds for characterizing student-driven Earth system citizen science investigations. Secondarily, this study aimed to capture GLOBE’s alignment to existing citizen science outcomes frameworks in the literature, which have primarily focused on adults and non-formal settings. Based on a literature review, the evaluation team identified 89 potential characteristics in 27 categories to typify investigations from both formal education and citizen science perspectives. We coded the artifacts from 207 student projects, conducted quantitative analysis of frequencies, and performed a semantic network analysis. By using this networking approach, we conceptually mapped several clusters of co-occurring characteristics, defining a descriptive framework for GLOBE projects. We identified three tiers of citizen science projects, increasing in the sophistication of participants’ demonstrated science practices. The framework includes additional components that reflect student citizen scientists’ thoughtfulness and connection to context as well as their projects’ reflection of their motivation and self-efficacy. Through these findings, we have identified areas where student citizen scientists would benefit from further support, and suggest here further research to incorporate the experiences of students into the broader understanding of citizen science outcomes.